Effects of sublethal application of Deepwater Horizon oil to bird eggs on embryonic heart and metabolic rate. Issue 5 (17th June 2020) - Goodchild, Christopher G.; Grisham, Kevin; Belden, Jason B.; DuRant, Sarah E.
Abstract: Following large crude oil spills, oil from feathers of brooding birds and oiled nesting material can transfer to eggs, resulting in reduced embryonic viability for heavily oiled eggs. Eggs may also be subjected to trace or light oiling, but functional teratogenic effects from sublethal crude oil exposure have not been examined. We assessed whether sublethal application of weathered Deepwater Horizon crude oil to the eggshell surface alters heart rate and metabolic rate in Zebra Finch ( Taeniopygia guttata ) embryos. We first determined sublethal applications with a dosing experiment. Embryo viability for eggs exposed to 5 μL or more of crude oil decreased significantly. We conducted a second experiment to measure heart rate and metabolic rate (CO2 production) 5 and 9 d after 1 sublethal application of crude oil to eggshells on day 3 of incubation. One application of 1.0 or 2.5 µL of crude oil reduced embryonic heart rate and metabolic rate on day 12 of incubation. Using unfertilized eggs, we measured the transfer of polycyclic aromatic hydrocarbons (PAHs) from the eggshell surface to egg contents 9 d after a single application of sublethal crude oil. Our results suggest avian eggs externally exposed to small amounts of crude oil may exhibit protracted embryonic development and impaired postnatal cardiac performance. Abstract : Article impact statement : Sublethal embryonic effects of crude‐oil exposure may impair recovery of bird populations after an oil spill. Abstract : Aplicaciones Subletales de Petróleo de la Plataforma Deepwater Horizon en los Huevos de Aves y sus Efectos sobre la Frecuencia Cardíaca y la Tasa Metabólica de Embriones Resumen: Después de grandes derrames de crudo, el petróleo que se encuentra en las plumas de las aves incubadoras y el petróleo adherido al material para nidos puede transferirse a los huevos, lo que resulta en la reducción de la viabilidad embrionaria en el caso de los huevos con un contacto alto con el petróleo. Los huevos también pueden estar sujetos a manchas de petróleo ligeras o por contacto, pero no se han examinado los efectos teratogénicos funcionales de la exposición subletal al crudo. Evaluamos si la aplicación subletal de petróleo crudo desgastado del derrame de la plataforma Deepwater Horizon a la superficie de los cascarones altera la frecuencia cardíaca y la tasa metabólica de los embriones de gorrión cebra ( Taeniopygia guttata ). Primero determinamos las aplicaciones subletales con un experimento de dosificación. La viabilidad de los embriones en huevos expuestos a 5 µL o más de crudo disminuyó significativamente. Realizamos un segundo experimento para medir la frecuencia cardíaca y la tasa metabólica (producción de CO2 ) cinco y nueve días después de una aplicación subletal de crudo a los cascarones durante el tercer día de incubación. La aplicación de 1.0 o de 2.5 µL de crudo redujo la frecuencia cardíaca y la tasa metabólica al décimo segundo día de incubación. También medimos la transferencia de hidrocarburos aromáticos policíclicos (PAHs) en huevos sin fertilizar desde la superficie del cascarón hasta el contenido del huevo nueve días después de una aplicación subletal única de crudo. Nuestros resultados sugieren que los huevos de aves expuestos externamente a pequeñas cantidades de crudo pueden tener un desarrollo embrionario prolongado y un desempeño cardíaco postnatal deteriorado. 摘要: 大规模原油泄漏后, 孵蛋鸟类羽毛上的油污和受污染筑巢材料中的油污会转移到鸟蛋上, 导致油污严重的鸟蛋胚胎存活率降低。鸟蛋也可能受到微量或轻度的原油污染, 但亚致死原油暴露的功能性致畸效应尚未得到检验。我们评估了经风化的"深水地平线号"原油在蛋壳表面的亚致死涂污是否会改变斑胸草雀 ( Taeniopygia guttata) 胚胎的心率和代谢率。我们首先通过剂量试验确定了亚致死涂污量。暴露在 5μL 及以上的原油中的鸟蛋胚胎活力显著下降。我们进一步在孵育第三天的鸟蛋壳上进行亚致死涂污处理, 并在第五天和第九天测量其心率和代谢率 (CO2 产量) 。 1.0 或 2.5 μL 的原油涂污会降低孵育 12 天胚胎的心率和代谢率。利用未受精的鸟蛋, 我们测量了单次亚致死原油涂污 8 天后多环芳烃从蛋壳表面到蛋内容物中的转移情况。我们的结果表明, 外部暴露于少量原油中的鸟蛋可能会延长胚胎发育时长, 且出生后的心脏功能受损。 【翻译: 胡怡思; 审校: 聂永刚】